Analysis of Morphological Characteristics of Soybean Varieties (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Nowadays, the demand for soybeans has been increasing in many countries around the world. Soybean plant is considered to have many beneficial properties for humans and food. Its grain is one of the most valuable crops and is more expensive than other crops because it contains 50% protein and up to 28% oil. Today, more than 400 different products necessary for the national economy are made from soybeans. The article analyzes the morphological characteristics of "Akcent" and "Uzbek-6" soybean varieties without mineral fertilizers. In the results of the analysis, it was noted that the disparity between the characters mainly depends on the genotype.